2004
DOI: 10.1177/0306624x03261559
|View full text |Cite
|
Sign up to set email alerts
|

Social Climate within an Adolescent Medium-Secure Facility

Abstract: The objectives of the study were to investigate the social climate of two different types of units (open vs. secure) contained within the same South London adolescent medium-secure facility. Two hypotheses were generated: (a) adolescents would rate the social climate of the whole facility in a more negative direction than staff and (b) adolescents and staff would rate the social climate of the open units in a more positive direction than the social climate of the secure units. 43 adolescents and 49 staff membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
4
24
1
1
Order By: Relevance
“…Finally, the residents within more secure hospital settings were rated as less cohesive and supportive of each other than residents from conditions of lesser security, and the residents within more secure prison settings rated their unit as less safe than those from less secure prisons. These findings make sense theoretically and fit with the general pattern of findings observed in previous research using the EssenCES Howells et al, 2009;Long et al, 2010;Schalast et al, 2008) and with research using the WAS/CIES (Friis & Helldin, 1994;Langdon, Cosgrave, & Tranah, 2004;Langdon, Swift, & Budd, 2006;Moos & Schaefer, 1987).…”
Section: Validation Of the English Essences 16supporting
confidence: 86%
“…Finally, the residents within more secure hospital settings were rated as less cohesive and supportive of each other than residents from conditions of lesser security, and the residents within more secure prison settings rated their unit as less safe than those from less secure prisons. These findings make sense theoretically and fit with the general pattern of findings observed in previous research using the EssenCES Howells et al, 2009;Long et al, 2010;Schalast et al, 2008) and with research using the WAS/CIES (Friis & Helldin, 1994;Langdon, Cosgrave, & Tranah, 2004;Langdon, Swift, & Budd, 2006;Moos & Schaefer, 1987).…”
Section: Validation Of the English Essences 16supporting
confidence: 86%
“…Other terms that have been used include the "social environment" (Smith et al 1997), "climate perceptions" (Parker et al 2003), "workplace climate" (Carr et al 2003), and the "ward climate" (Stevens 1961). In addition, a myriad of social climate concepts can be found in the management, work and organisational psychology, and medical literatures (e.g., Dollard & Bakker 2009;Garrett & McDaniel 2001;Langdon et al 2004;Langdon et al 2006;Moos & Bromet 1978;Ulrich et al 2007). In some studies no definition of climate is provided (e.g., Howells 2000; Nesset et al 2009;Schalast et al 2008), suggesting that there is a need for researchers to use terminology that is consistent with their approach to measurement, theory, and analysis.…”
Section: Therapeutic Prisonsmentioning
confidence: 99%
“…Research conducted in forensic mental health settings has often focussed on the connection between social climate and treatment outcomes; in other words, how the perception of the social environment impacts upon patient care (Clarke et al 2002a;Gelade & Ivery 2003;Griffin et al 2010;Kangis et al 2000;Langdon et al 2004;Langdon et al 2006;Moos & Bromet 1978;Pritchard & Karasick 1973). One study by Arnetz and Arnetz (2001) found that fear of violence experienced by health care staff was negatively and significantly related to patientreported quality of care.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Caplan (1993) found that staff and patient perceptions differed with regard to several scales of the Ward Atmosphere Scale (WAS; Moos, 1968;1989, Moos & Houts, 1974, including order and organization, program clarity and staff control. Possible explanations given in previous research for the divergent perceptions between nursing staff and patients are, the different roles and functions that staff and patients have within a forensic institution (Caplan,1993;Goffman, 1961;Rossberg & Friis, 2004), and the restrictions to the liberty and personal freedom of incarcerated patients (Langdon, Cosgrave & Tranah, 2004). Patients' restricted liberty could also be a potential explanation for the finding that the perception of climate differs as a function of the level of security (Dickens et al, 2014;Long et al, 2011;Milsom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%